RESEARCH ON OPTIMIZATION OF HEAVY LOAD RAILWAY RAIL GRINDING PROFILE BASED ON ABRASION CONTROL - YANG YiHang; LIU XueShen; LIU JiHua (Jixie qiangdu)
Wa-ri heavy load railway is taken as the research object in the paper,the rail profiles are observed before and after grinding. Based on the wheel/rail contact wear theory and the finite element model of high-speed wheel/rail steady rolling contact established by the mixed Lagrangian/Eulerian method,the four kinds of railway grinding profile are contacted with LM wheels,the optimal rail profile was selected. Results show that,the profile 1 TQI and wear rate are the maximum,When the profile 1 contact with LM,the distribution of contact point pairs is relatively concentrated,equivalent conicity is largest,the mass flow density and wear power maximum are the biggest,wheel/rail wear is biggest. the profile 3 TQI and wear rate are the minimum,the contact point distribution between profile 3 and LM tread is good,equivalent conicity is least,the mass flow density and wear power maximum are the least. Therefore,only from the perspective of wear control,the research shows that the profile 3 is the optimal grinding profile.